RECONSTRUCTING THE ROLE OF JUDGES IN INDONESIAN CIVIL PROCEDURAL LAW: BETWEEN THE PRINCIPLE OF JUDICIAL PASSIVITY AND PROCEDURAL JUSTICE - Pri Pambudi Teguh (Legal Standing : Jurnal Ilmu Hukum, 2026)
Indonesian civil procedural law remains strongly influenced by colonial legal paradigms that position judges as passive actors strictly bound by the parties’ claims. In judicial practice, the formalistic application of the passive judge principle frequently generates problems of procedural justice, particularly when litigation is terminated on procedural grounds without substantive examination. This condition is problematic within a rule-of-law framework that requires courts to uphold justice and the protection of rights. This study aims to examine the normative construction of the passive judge principle in Indonesian civil procedure and to formulate a reconstruction of the judicial role capable of ensuring procedural justice without undermining judicial impartiality and legal authority. This research employs normative legal research using statutory and conceptual approaches, analyzed through qualitative descriptive methods. The findings indicate that the passive judge principle cannot be interpreted absolutely, as it must be understood systemically within the framework of the rule of law and the purposes of law. Furthermore, a reconstruction of the judicial role through the measured use of judicial discretion is necessary to prevent civil litigation from being trapped in procedural formalism and to ensure a balanced realization of justice, legal certainty, and utility.